Trinidad and Tobago, West Indies - Parkinson, Norman (My University, 2010)
Description on the back of the postcard: "A Ruby Topaz hummingbird flies back to her nest and her hungry chicks. The nest is well camouflaged, built on a branch of Croton bush. (Chrysolampus Mosquitus). This image is copyrighted to Norman Parkinson.
Colour: Coloured (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Ruby-topaz Hummingbird; Chrysolampis mosquitus; Birds